Development of a new system to control and monitor ground vehicles using heterogeneous mobile networks - Murilhas, Luis Carlos Margaço (2016)
The Unmanned Vehicle Systems (UVS) are growing in large proportions and are an emerging technology but there are some limitations that still need to be overcome in order to get the best effectiveness. One of the limitations is the reception area for vehicle operation. Most vehicles operate in line-of-sight (LOS). A very significant improvement would be to allow behind line-of-sight (BLOS) operation via wireless networks. This thesis proposes to overcome this difficulties using wireless networks: Wi-Fi and third generation (3G) and fourth generation (4G) of mobile networks to operate an Unmanned Ground Vehicle (UGV), also called a rover. This way, the vehicle will not have a theoretical range operation, turning into a vehicle operated in BLOS. This thesis also includes the study of the reliability and efficiency of wireless heterogeneous networks solution for UGVs operation in real time. As prove of concept for described objectives, an Unmanned Ground System (UGS) was developed. This system is capable of control and monitoring multiple vehicles through wireless networks: Wi-Fi, 3G and 4G mobile networks. The communication between the vehicle and the operator is made through a ground control station (GCS), an Android application running on a mobile device. Its aim is to centralize all the information from the vehicle(s). Present on the vehicle is a Raspberry Pi (RPI) acting like a proxy, thus enabling the communication between the GCS application and the UGV’s board controller, the Ardupilot Mega (APM). The RPI receives telemetry from APMviaMicro Air Vehicle Communication Protocol (MAVLink) and captures video through an external camera and sends it all to the GCS. In order to evaluate the system performance, several tests were done for data collection, namely values of network latency, bitrate, packet error ratio (PER) and signal strength varying with speed, altitude and location of the vehicle.